Multi Contract as A Legal Justification of Islamic Economic Law for Gold Mortgage Agreement in Islamic Bank - Yusup, Deni Kamaludin (SCAD Independent, 2019)
In recent years, the gold mortgage agreement has become one of the excellent products in Islamic banks. Practically, the gold mortgage agreement to the customer uses the principle of qard with the guarantee of gold in question through the pledge agreement (al-rahn). Gold as a property shall be the object of debt security placed in the control and maintenance of the Islamic bank with certain fee (al-ijarah). The selected object is focused on the multi-contract of gold mortgage agreement at PT. Bank Syariah Mandiri Tbk. This research uses the combination between bibliographical and empirical methods which is supported by primary and secondary data from relevant literature and interview with the informan, and also analysis of the data uses deductive-inductive approach. The result of this study indicates that gold mortgage agreement at PT. Bank Mandiri Syariah used sharia multi-contract or mutanaqishah contract, in which there were combining gratuitous contract (al-tabarru’) and compensational contract (al-tijarah). In the classical Islamic economic law perspective, it looks like a legal justiciation (hilah syar’iyyah) which prohibited taking the excessive benefits from the provision of additional debt (al-ziyadah) and other benefits to cover usury in the practice of ujrah for custodial services, but some opinion of legal jurits allowed it based on the reason that it is included in hilah syar’iyyah mahmudah and also relevant to the principle of adillah al-syar’iyyah and Fatwa DSN-MUI Number: 25/DSN-MUI/III/2002 on Rahn, Article 1320 Civil Code, and the Islamic Banking Law Number 21 of 2008.